A Review on Viscometer Devices for Gas Phase - Elin Yusibani (Aceh International Journal of Science and Technology)
Abstract -Viscosity, one of the transport properties, is a basic property required for developing any device in which fluid flows. In the present paper, major gas viscometers devices are reviewed. The review is covering to the pressures and the temperatures ranges, methods and accuracy of the instruments, and the coefficient of viscosity-range of the sample. This study is expected become useful information for any researcher who wants to develop a gas viscometer apparatus in a near future. By identifying the coefficient of viscosity-range and the  easurement-range of temperatures and pressures, then we can choose the effective and efficient method to be developed.